Property crime prevention in Malaysian housing: Issues and challenges - Saidul Kurzi, Nurfadilah; Sapian, Abdul Razak; Mohd. Yaman, Maheran (2009)

(untitled)
This paper will review the background of housing in Malaysia. It covers the current housing industries includes the planning and design implementation. This paper will look into the current crime scenario regarding on the causes, effects and the outcomes, with the focus on property crime. It will then deeply elaborate the Crime Prevention through Environmental Design (CPTED) subjecting to its necessity, current application, efficiency and current demand. Based on the reviews, this paper is aimed to discover the effectiveness of this approach and to put forward on the alternative solution that can be imply in Malaysian housing pattern so that an eminent security level with aesthetical design can be improved.